TRANSFORMATION OF COMMUNITY CAPACITY THROUGH EDUCATION-BASED EMPOWERMENT IN PT PERTAMINA EP SANGA-SANGA CSR PROGRAM IN THE SUNGAI HITAM SAMBOJA ECOTOURISM AREA - Jumriah Agustina; Mustangin; Muhamad Alisalman; Arif Sugianto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the empowerment strategy in the Sungai Hitam Lestari Ecotourism area by PT Pertamina EP Sanga-Sanga Field's CSR. The focus of this research is on three stages in education-based empowerment, namely the awareness stage, the ability transformation stage and the intellectual ability stage. A qualitative approach with a descriptive method was carried out in this study. The data collection used interview, observation and documentation study methods. Data analysis is carried out by means of data reduction, data presentation and conclusion drawn. Research results At the awareness stage, social mapping was carried out, collaboration with the government and local community groups such as Pokdarwis, forming MSMEs and WWTP Groups in expanding empowerment goals, and providing education for these groups. The ability transformation stage is realized through non-formal education, namely trainings such as financial management, English language training, tour guides, processed mangrove products, eco enzymes, and floating WWTP management. The training was prepared in a participatory manner, intensely monitored and evaluated through the Community Satisfaction Index (IKM). At the intellectual ability stage, the community begins to be independent through regeneration, impact measurement (SROI, BOD, COD), and cross-sector collaboration. The results show an increase in proboscis monkeys, an increase in group income, strengthening local capacity, reducing emissions and waste, and the sustainability of ecotourism management after the CSR program ends.